Bullous morphea – a case report - Bergler-Czop, Beata; Brzezińska-Wcisło, Ligia; Meszyńska, Elżbieta (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction . Bullae occurring in morphea lesions are uncommon and their cause is multifactorial. One of the possibilities is lymphatic obstruction as a result of a sclerodermatous fibrotic process. Bullous morphea may be confused clinically with lichen sclerosus et atrophicus since in both diseases bullae in sclerodermatous plaques can be observed. Objective . To present a rare case of bullous morphea in which bullae within indurated plaques developed 15 years after the onset of the disease. Case report . Female 41 years old. First indurated plaque started to develop at the age of 26 and 15 years later in morphea lesions appeared numerous tense bullae. Physical examination revealed multiple erythematous erosions, haemorrhagic vesicles and eroded bullae with slight scaling or crusts overlying hypopigmented, indurated, shiny plaques. Skin biopsy revealed prominent oedema in the papillary dermis, resulting in bulla formation. Immunological examination (direct and indirect immunofluorescence) was negative. According to histopathological and clinical features, the diagnosis of bullous morphea was established. The patient was treated for 40 days with cephalosporins with good results (bullae stopped developing). Conclusion . Bullous morphea is a rare variety of cutaneous scleroderma and should be differentiated from lichen sclerosus et atrophicus and autoimmune subepidermal bullous diseases. Bullae within indurated morphea plaques can develop even many years after the onset of the disease.